INVESTIGATION OF THE PATHOLOGICAL EFFECTS OF EXTRACELLULAR DNA AND HISTONES IN SEPSIS - MEDEIROS, SARAH K (My University, 2023)
Sepsis is defined as a life-threatening organ dysfunction that results in systemic activation of coagulation and inflammation in response to microbial infection. Neutrophil extracellular traps (NETs) have shown to be an important interface between innate immunity and coagulation in sepsis. The major structural components of NETs are nucleosomes (DNA-histone complexes). Although nucleosomes do not modulate coagulation, there are conditions where DNA and histones dissociate from each other in the circulation (e.g. in the presence of heparan sulfate or therapeutic heparin binding histones, or DNase digestion of DNA). In vitro, purified DNA was reported to activate coagulation, but this procoagulant activity has been questioned due to isolation methods that yield DNA that is contaminated with other procoagulant molecules. On the other hand, histones have been shown to not only activate coagulation but are cytotoxic to endothelial cells. However, their contribution to the pathogenesis of sepsis has yet to be determined in an in vivo model. Understanding the contribution of DNA, histones, and nucleosomes to the pathogenesis of sepsis may allow us to develop novel therapies that may prove targeting multiple components of NETs (i.e. DNA and histones) may be beneficial. Consequently, in this thesis, we (1) identified methods of DNA purification that produce DNA that is free of contamination and confirmed the procoagulant properties of the isolated DNA, (2) determined the harmful effects of DNA, histones, and nucleosomes cytotoxicity, coagulation, and inflammation in vitro and in vivo, (3) and then we explored the possibility of targeting both DNA and histones using a combination approach of DNase I and heparin in a mouse model of sepsis. Since heparin is administered to patients as a thromboprophylaxis and DNase I is a potential therapy in sepsis, it is important to understand any potential drug-drug interactions.
Keywords: SEPSIS; DNA; HISTONES; NUCLEOSOMES; MOUSE; COAGULATION; INFLAMMATION; SURVIVAL; DNASE I; HEPARIN